Pemetaan Sebaran Titik Panas (Hotspot) Tahun 2017-2021 Di Kota Batam - Putri Ariani Trestiyan; Arif Roziqin (Politeknik Negeri Batam, 2022)
The city of Batam has a bush area that is quite extensive so that this can trigger forest and land fires in the city of Batam. The city of Batam has quite hot weather so that it is one of the factors that cause forest fires. The purpose of this study is to determine the distribution of the value or number of hotspots in 2017-2021 in Batam City and to determine the distribution of hotspots to land cover in 2017-2021 in Batam City. This study uses several data, namely MODIS image hotspot data sourced from the National Aeronautics and Space Institute (LAPAN) for 2017-2021, a map of land cover distribution and an administrative map of Batam City. The initial data processing process in this research is to convert MODIS image hotspot data obtained from the National Institute of Aeronautics and Space (LAPAN) with .csv format into .shp format for further overlaying with a land cover map, after that perform a gridding process that aims to to get the distribution of values or the number of hotspots. From the results of MODIS image hotspot data sourced from the National Institute of Aeronautics and Space (LAPAN) during 2017-2021 there are 119 hotspots located in 22 clusters in an area of 1km x 1km and during 2017-2021 it is known that the number of hotspots (hotspots) in the scrub area there are 8 hotspots in forest areas there are 6 hotspots and in non-forest areas there are 105 hotspots.